Performance comparison of state-of-the-art deep learning model architectures in Indonesian food image classification - Rasyidi, Mohammad Arif; Mardhiyyah, Yunita Siti; Nasution, Zuraidah; Wijaya, Christofora Hanny (Bulletin of Electrical Engineering and Informatics, 2024)
Food image recognition is essential for developing an elderly-friendly daily food recording application in Indonesia. However, existing datasets and models are limited and do not cover the diversity and complexity of Indonesian food. In this paper, we present a new dataset of 24,427 images of 160 types of Indonesian food with higher variety and quality than previous datasets. We also train and compare the performance of 67 models based on 16 state-of-the-art deep learning architectures on this dataset. We find that efficientnet_v2_l provides the best accuracy of 85.44%, followed by other models such as convnext_large and swin_s. We also discuss the trade-off between model size and performance, as well as the challenges and limitations of food image classification. Our dataset and models can serve as a basis for developing a user-friendly and accurate food recording application for the elderly population in Indonesia.